Small business revolution how owners and entrepreneurs can succeed - McCarthy, Barry C. (Ascent Audio, 2022)
In Small Business Revolution president and CEO of Deluxe Corp. Barry C. McCarthy delivers a stirring combination of uplifting narrative and small business instruction manual. Featuring inspiring stories from the company's 106-year history and anecdotes from its Emmy-nominated TV show Small Business Revolution, this book offers listeners the opportunity to learn how to grow and thrive in their business in any environment, from a booming economy to a post-pandemic marketplace. Whether you're just starting to plan your new business or you are a seasoned veteran in the small business trenches, you'll discover a wealth of information to help you structure your business to reach customers, find talent, understand finances, and so much more. You'll find guidance on: how to get your costs in line when your expenses have changed; mastering new tools to manage payments and payroll, including contactless and remote payments; maintaining relationships with your existing customers while reaching out to new ones; how to manage cash; how to retain employees through lean times; and more. Perfect for the millions of individuals who plan to start or run a small business during one of the most challenging times in recent memory, Small Business Revolution is an indispensable guide to helping your enterprise survive and succeed during unprecedented challenges.